2011
DOI: 10.1029/2010jb008053
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-dependent streaming potential of Ottawa sand

Abstract: [1] The scientific literature is almost devoid of frequency-dependent electrokinetic measurements on geological materials. An apparatus that allows the measurement of the streaming potential coupling coefficient of unconsolidated and disaggregated materials such as sands, gravels, and soils has been designed, constructed, and tested. The apparatus, which uses an electromagnetic drive, operates in the range 1 Hz to 1 kHz and has a 25.4 mm diameter sample chamber for samples up to 150 mm long. We have made strea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 20 publications
3
44
0
Order By: Relevance
“…However, a recent study showed that the simplification is incorrect [11]. The correct simplification, which is consistent with the simplified model solution shown in their Figure 4 [9] (T. Ishido, pers.…”
Section: Capillary Tube Modelssupporting
confidence: 78%
See 1 more Smart Citation
“…However, a recent study showed that the simplification is incorrect [11]. The correct simplification, which is consistent with the simplified model solution shown in their Figure 4 [9] (T. Ishido, pers.…”
Section: Capillary Tube Modelssupporting
confidence: 78%
“…Its disadvantage is that a high-quality harmonic driving pressure is required to create the time-varying flow. Various authors have shown that measurements on a range of materials are possible in the range 1 Hz to 600 Hz [6][7][8][9][10], but before the recent paper of Tardif et al [11] only one measurement had been made on a geological material [10].…”
Section: Introductionmentioning
confidence: 99%
“…Glover et al (2006) collated a database of C sp and ζ determinations as a function of salinity, which is reproduced in Fig. 1 with supplementary data from AC measurements on Ottawa sand (Tardif et al 2011;Glover et al 2012a), and omitting carbonate samples. Four aspects of the data are worth mentioning explicitly.…”
Section: Introductionmentioning
confidence: 99%
“…(Sprunt et al 1994;Pozzi 1995a, 1997;Li et al 1995;Jiang et al 1998;Pengra et al 1999); [2] sandstone with NaCl as a function of permeability/microstructure (pH5) (Jouniaux and Pozzi 1995b); [3] St. Bees, Stainton, and Fontainebleau sandstones with NaCl (Jaafar et al 2009;Vinogradov et al 2010); [4] sandstone with KCl (Alkafeef and Alajmi 2007); [5] sand with NaCl (Guichet et al 2003;Block and Harris 2006);[6] granite with NaCl (Morgan et al (1989)); [7] glass with NaCl (Pengra et al 1999;Block and Harris 2006);[8] zeolitized tuffs with NaCl (Revil et al 2002);[9] basalt with NaCl (Revil et al 2003 (Tardif et al 2011;Glover et al 2012a). b [1] Quartz with NaCl (Pride and Morgan (1991)); [2] silica with NaCl (Gaudin and Fuerstenau 1955;Li and Bruyn 1966;Kirby and Hasselbrink 2004);[3] glass beads with NaCl (Bolève et al 2007);[4] St.…”
Section: Introductionmentioning
confidence: 99%
“…So the frequency dependence of the streaming potential coefficient has been studied (Packard, 1953;Cooke, 1955;Groves and Sears, 1975;Sears and Groves, 1978;Chandler, 1981;Reppert et al, 2001;Schoemaker et al, 2007Schoemaker et al, , 2008 mainly on synthetic samples, and recently on sand (Tardif et al, 2011), and on unconsolidated materials (Glover et al, 2012). In 1953 Packard (1953) proposed a model for the frequency-dependent streaming potential coefficient for capillary tubes, assuming that the Debye length is negligible compared to the capillary radius, based on the Navier-Stokes equation:…”
Section: Frequency-dependence Electrokineticsmentioning
confidence: 99%